Epigenetics alternation in lung fibrosis and lung cancer - Li, Xueren; Feng, Chunjing; Peng, Shouchun (Frontiers in Cell and Developmental Biology, 2022)
Respiratory disease including interstitial lung diseases (ILDs) and lung cancer is a group of devastating diseases that linked with increased morbidity and healthcare burden. However, respiratory diseases cannot be fully explained by the alternation of genetic information. Genetic studies described that epigenetic mechanisms also participate to transmit genetic information. Recently, many studies demonstrated the role of altered epigenetic modification in the pathogenesis of lung cancer and pulmonary fibrosis. Due to lacking effective medication, the underlying pathophysiological processes and causal relationships of lung diseases with epigenetic mechanisms still need to be better understood. Our present review provided a systematic revision of current knowledge concerning diverse epigenetic aberrations in major lung diseases, with special emphasis on DNA methylation, histone modifications, lncRNAs profiles, telomere patterns, as well as chromatin-remodelling complexes. We believed that a new target therapy for lung disease based on findings of the involved epigenetic pathway is a promising future direction.